Forschungsperspektiven der Geschichte des regionalen Genossenschaftswesens am Beispiel der Provinz Posen - Patrick Bormann (IBF - Institut für Bank- und Finanzgeschichte e.V., 2020)
Despite the recent increase in research on the history of the system of German cooperative banks, the middle tier of the three-level cooperative system has remained a blind spot. The lack of sources has been alleviated by the discovery of the long forgotten archive collection I. HA, Rep. 177 of the Geheimes Staatsarchiv Preußischer Kulturbesitz, which contains the business files of the Preußische Zentralgenossenschaftskasse (Preußenkasse), as well as records of the Prussian Ministry of Agriculture, which had previously gone unnoticed. Using the Poznan cooperative system as an example, the following article shows the potential that lies in a more intensive analysis of the regional cooperative organizations. Such analyses would not only provide new insights into the creation, development and competition of regional associations. They would also enable new insights into the networking of cooperatives with other organizations and movements, into conflicts arising from the development of a new economic infrastructure and into the social profile of the actors involved, about whom little is known at present. The study of the cooperative system in Poznan shows how important a history of the influence of the Preußenkasse as the central agricultural instrument of Prussia would be. The bank derived its influence not only from its founding motives or business policy, but also to a large extent from local circumstances and local actors.
Keywords: N23; N24; 330